Differential Effects of Alpha-Particle Radiation and X-Irradiation on Genes Associated with Apoptosis - Vinita Chauhan; Matthew Howland; Jeremy Chen; Barbara Kutzner; Ruth C. Wilkins (Radiology Research and Practice)
This study examined differential effects of alpha-(α-) particle radiation and X-rays on apoptosis and associated changes in gene expression. Human monocytic cells were exposed to α-particle radiation and X-rays from 0 to 1.5 Gy. Four days postexposure, cell death was measured by flow cytometry and 84 genes related to apoptosis were analyzed using real-time PCR. On average, 33% of the cells were apoptotic at 1.5 Gy of α-particle radiation. Transcript profiling showed statistical expression of 15 genes at all three doses tested. Cells exposed to X-rays were <5% apoptotic at ~1.5 Gy and induced less than a 2-fold expression in 6 apoptotic genes at the higher doses of radiation. Among these 6 genes, Fas and TNF-α were common to the α-irradiated cells. This data suggests that α-particle radiation initiates cell death by TNF-α and Fas activation and through intermediate signalling mediators that are distinct from X-irradiated cells.